Impact of self-perceived discomfort in critically ill patients on the occurrence of psychiatric symptoms in post-intensive care syndrome (PICS): A prospective observational study - Romain Ronflé; Julie Hermitant; Christine Conti-Zolin; Laurent Lefebvre; Thibault Helbert; Aurélien Culver; Florence Molenat; Baptiste Borwel; Mohamed Boucekine; Pierre Kalfon; Marc Leone (PLoS ONE, 2025)
Background Mental health impairments after intensive care unit (ICU) discharge include anxiety, depression, and post-traumatic stress disorder [PTSD], forming part of the post-intensive care syndrome (PICS). We assessed the effects of discomfort on the occurrence of psychiatric symptoms as a part of PICS. Methods This prospective observational study conducted from September 2022 to June 2023 included all patients aged ≥ 18 years who survived an ICU stay of ≥3 days. To assess patient discomfort during the ICU stay, we used the Inconforts des Patients de REAnimation (IPREA) questionnaire. The primary outcome was the occurrence of anxiety, depression, or PTSD after ICU discharge. Secondary outcomes were the quality of life in ICU survivors and the clinical impression of physicians and psychologists to predict post-ICU psychiatric symptoms. Results Of the 173 patients included initially, 109 were finally analysed. An IPREA score ≥ 13 was strongly associated with an increased risk of post-ICU psychiatric symptoms (odds ratio: 3.8, 95% confidence interval: 1.4–10.3, p = 0.008). The patients with post-ICU psychiatric symptoms had a reduced quality of life. The clinical impression of physicians and psychologists at ICU discharge for the risk of psychiatric symptoms 3 months after the ICU stay was not selective. Conclusions Self-perceived discomfort in ICU survivors was the most predictive factor of the development of post-ICU psychiatric symptoms.